Perancangan dan Pembuatan Program Simulasi Kesetimbangan Termodinamika untuk Proses Gasifikasi Biomassa - Hari Rionaldo; Zulfansyah; Mazlani (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2021)
The non-stoichiometric thermodynamic equilibrium simulation program for the biomass gasification process was developed using the Python programming language. It is featured with a GUI (Graphical Users Interface), to facilitate user interaction. The program is designed to calculate the composition of gas producer with 6 components involved, they are CH4, CO, CO2, H2, N2, and H2O. The design of computational algorithms for calculating non-stoichiometric thermochemical equilibrium models is converted into Python code. The GUI consists of input and output facilities in form of tables and graphs of calculation results. The input facility is designed in such a way that the user can vary the gasification temperature and the equivalent ratio. The calculation results of the simulation program are verified with the calculated data manually to ensure that there are no errors in the algorithm or writing program code. It is also compared with the experimental data from previous studies to see the accuracy of the thermodynamic model in predicting the composition of gas producer. The non-stoichiometric thermodynamic equilibrium simulation program for the biomass gasification process can predict the composition of producer gas with a fairly good level of accuracy and can be used as a learning medium in studying thermodynamic equilibrium.